An anonymous access authentication scheme for vehicular ad hoc networks under edge computing - Tianhan Gao; Yanqiang Li; Nan Guo; Ilsun You (International Journal of Distributed Sensor Networks)
With the rapid booming of intelligent traffic system, vehicular ad hoc networks have attracted wide attention from both academic and industry. However, security is the main obstacle for the wide deployment of vehicular ad hoc networks. Vehicular ad hoc networks security has two critical issues: access authentication and privacy preservation. How to ensure privacy preservation and improve the efficiency of authentication has become the urgent needs. However, the existing access authentication schemes for vehicular ad hoc networks with different flaws cannot maintain the balance between security and efficiency. Thus, an anonymous access authentication scheme for vehicular ad hoc networks under edge computing based on ID-based short group signature mechanism is proposed in this article to improve the efficiency and anonymity of access authentication. Multiple pseudonyms are presented to preserve the privacy of vehicle node. Besides, a new method is designed to identify and revoke malicious vehicles in the evaluation manner. The core protocols of the proposed scheme are proved to be secure by SVO logic. According to the computation cost and transmission overhead analysis, we indicate that our scheme owns better performance. Moreover, in this article, we combine vehicular ad hoc networks with edge computing together to provide a new clue for the development of mobile edge computing.